2022
DOI: 10.1007/s00268-022-06755-y
|View full text |Cite
|
Sign up to set email alerts
|

Label‐Free Enhancement of Adrenal Gland Visualization Using Near‐Infrared Autofluorescence for Surgical Guidance

Abstract: Background During adrenalectomy, surgeons have traditionally relied on their subjective visual skills to distinguish adrenal glands (AGs) from retroperitoneal fat and surrounding structures, while ultrasound and exogenous contrast agents have been employed for intraoperative AG visualization, all of which have their limitations. We present a novel label‐free approach that uses near‐infrared autofluorescence (NIRAF) detection, which demonstrates potential for enhanced intraoperative AG visualization and efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The results of our study strengthen the previously published, yet smaller initial experiences published at three separate academic, high-volume adrenal institutions, including our institution, that benign adrenocortical tumors exhibit significantly more intense AF compared with pheochromocytomas and malignant tumors. [11][12][13] In our initial study, the average AF for all benign adrenocortical tumors was 2.23 (n = 16), for pheochromocytomas was 0.90 (n = 3), and for malignant tumors was 0.90 (n = 5). 11 While the normalized AF values calculated in the current study are slightly higher compared with our initially published experience using the same commercially available NIRAF imaging system, the trend remains the same.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The results of our study strengthen the previously published, yet smaller initial experiences published at three separate academic, high-volume adrenal institutions, including our institution, that benign adrenocortical tumors exhibit significantly more intense AF compared with pheochromocytomas and malignant tumors. [11][12][13] In our initial study, the average AF for all benign adrenocortical tumors was 2.23 (n = 16), for pheochromocytomas was 0.90 (n = 3), and for malignant tumors was 0.90 (n = 5). 11 While the normalized AF values calculated in the current study are slightly higher compared with our initially published experience using the same commercially available NIRAF imaging system, the trend remains the same.…”
Section: Discussionmentioning
confidence: 84%
“…Thomas et al in their series of 55 patients using another similar commercially available NIRAF imaging system, PDE-Neo II (760-nm camera), found benign adrenocortical tumors to also exhibit more intense AF compared with malignant tumors and pheochromocytomas, with ratios of 1.57 and 1.43 respectively. 12 Rajan et al, in their series of 22 patients also using the PDE-Neo II camera system, found benign adrenocortical tumors to harbor the most intense AF, with them being 1.50 times more intense than "suspicious/ growing" adrenal masses (final pathology not reported to confirm these were in fact malignant tumors) and 1.97 times…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improved visualization could be particularly helpful for low-volume surgeons, or in patients with excess visceral fat. This paper by Thomas et al [ 4 ], a collaboration between surgeons and engineers, is an elegant pilot study investigating the optical characteristics of normal and pathologic adrenal glands compared with surrounding structures, using commercial and custom-built cameras and handheld probes to assess fluorescence.…”
mentioning
confidence: 99%